(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the syntactic features of Ernest Hemingway’s novella “The Old Man and the Sea,” focusing on how his distinctive sentence structures contribute to the narrative’s minimalist style and thematic depth. By analyzing Hemingway’s use of simple and compound sentences, repetition, and parataxis, the study explores how these syntactic choices reflect the protagonist’s internal experiences and the broader existential themes of the work. Additionally, the article discusses the application of these findings in teaching reading through critical thinking, drawing on practical experiences from a lyceum setting with 2nd-course students.